Gas separation membrane
By incorporating the sheet-shaped Na-SSZ-39 zeolite filler into the Matrimid polymer matrix, the compatibility problem between zeolite and glassy polymer is solved, and a high-performance CO2 removal film is achieved, with ultra-high zeolite loading and selective, suitable for gas separation and carbon neutralization applications.
Patent Information
- Application Number
- CN202380042906.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-28
- Filing Date
- 2023-04-27
- Publication Date
- 2025-01-10
AI Technical Summary
The prior art faces compatibility problems between zeolites and glassy polymers when developing high-performance zeolite-filled mixed matrix membranes, resulting in poor non-selective interface voids and mechanical properties, making it difficult to achieve high zeolite loading and selective combinations.
Incorporate the sheet-shaped 8-membered ring AEI type Na-SSZ-39 zeolite filler into the Matrimid 5218 polymer matrix. By optimizing the synthesis process and the unique shape and adsorption behavior of the zeolite, avoiding the interfacial adhesion problem and achieving ultra-high zeolite loading High-performance CO2 removal film was prepared with a quantity and defect-free interface.
It achieves ultra-high CO2 removal performance, exceeding the previous MMM and pure zeolite membrane properties, showing excellent CO2-positive and gas separation properties, is flexible and aging-resistant, and is suitable for gas separation and carbon neutralization applications.
Smart Images

Figure CN119300907A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to membranes comprising zeolites and their use in gas or liquid separations. Background Art
[0002] Membrane technology has matured into an established commercial technology for CO2 separation in the past 30 years, finding applications in natural gas desulfurization and synthesis gas processing. In addition, the purification of biogas, the "net zero CO2" energy vector, and carbon capture from flue gas also have the potential to become important applications of membranes in the near future. Although more conventional technologies (such as amine absorption, cryogenic separation and adsorption) do have specific advantages, membrane technology can provide a more sustainable alternative, thanks to its low energy consumption, low environmental impact and modular design (allowing membrane modules to be refurbished in existing plants). Although polymers used to prepare commercial CO2-selective membranes are cheap and well processable, they suffer from inherent permeability / selectivity trade-offs, making it extremely challenging to obtain membranes with high permeability and sufficient selectivity combinations. On the other hand, inorganic membranes prepared by zeolites or by crystalline microporous hybrid materials (such as metal-organic frameworks (MOFs)) typically show better performance, but they have poor mechanical properties, are expensive, and face difficulties in processability and scalability. Therefore, there is still a need to develop new membrane materials for advanced separations to make gas separation methods more sustainable.
[0003] Mixed matrix membrane (MMM) is a hybrid membrane composed of fillers embedded in a polymer matrix. These membranes combine the processability, flexibility and low-cost advantages of polymers with the excellent gas separation properties of fillers. Many porous materials are studied as fillers for MMM, including zeolites, MOFs, carbon molecular sieves (CMS), covalent organic frameworks (COFs), graphene and carbon nanotubes (CNTs). Zeolites are particularly interesting for MMM development because they have well-defined, rigid pores combined with outstanding thermal, chemical and mechanical stability. Despite the huge theoretical potential of zeolites in MMMs, major obstacles have been encountered in polymer-zeolite compatibility. Because the inherent low selectivity and high permeability of rubbery polymers (such as polydimethylsiloxane (PDMS)) offset the benefits of zeolites, rigid glassy polymers are the key to developing high-performance zeolite-filled MMMs. However, the well-known poor interfacial adhesion between inorganic zeolites and rigid glassy polymers typically leads to non-selective interfacial voids. Therefore, achieving high zeolite loadings (>50 wt%) while ensuring a defect-free polymer-zeolite interface, combined with the selection of highly selective zeolites and a glassy polymer matrix can be considered as the main route to successful high-performance zeolite-filled MMMs for various most critical modern gas separation challenges. For example, flue gas applications should process large amounts of feed streams at low pressures, thus requiring high permeability membranes, while the multiple stages currently required in methane upgrading can benefit from membranes that are at least equally permeable but more selective. Summary of the invention
[0004] Herein, as an embodiment of the invention, a sheet-shaped 8-membered ring AEI type zeolite (SSZ-39) possessing a long-range ordered 3D connected micropore system with a gas selective window and excellent CO2 adsorption was incorporated into a Matrimid 5218 polymer matrix.
[0005] Thanks to the combination of a carefully optimized MMM synthesis procedure and the unique shape and adsorption behavior of the zeolite, the classical problem of poor zeolite-polymer adhesion is circumvented and ultrahigh zeolite loadings can be achieved, leading to unprecedented CO2 separation performances, surpassing those of all previously reported MMMs and even many pure zeolite or MOF-membranes.
[0006] As an example, developed for CO2 removal of ultra-high performance zeolite filled, polyimide-based membrane. This Na-SSZ-39 / Matrimid MMM shows the best CO so far from N2 and CH4 both the best CO2 removal performance, which is not only higher than any existing MMM, and even higher than pure zeolite membrane. By solving the compatibility problem between zeolite filler and glassy Matrimid matrix, prepared with defect-free zeolite / polyimide MMM greater than 50 wt % zeolite loading. Develop novel sheet-shaped Na-SSZ-39 zeolite as the filler for such film. Its excellent affinity for CO2 property (CO2-philicity), outstanding CO2 uptake capacity, competitive gas adsorption behavior of expectation and CH4 accurate size exclusion promotes the fabulous gas separation of film. In addition, thanks to the sheet shape of Na-SSZ-39 zeolite filler, obtained unique film morphology, this guarantees CO2 quasi-continuous permeation path, which greatly enhances the performance of film. The present invention not only relates to ultra-high performance CO2 removal membranes, but also demonstrates a feasible method for preparing defect-free zeolite-filled membranes with commercially available glassy polymers. It extends the application of zeolites to the membrane field and opens the door to the preparation of processable, robust, more scalable and economical high-performance zeolite-filled membranes, which is particularly beneficial for those zeolites that are quite difficult to convert into defect-free films. These membranes and their preparation techniques provide significant economic and environmental benefits for a global carbon neutral future.
[0007] In this article, mixed matrix membranes (MMMs) are studied to make energy-intensive separations more efficient by combining the selectivity and permeability performance, robustness and non-aging properties of fillers with the easy processing, handling and scale-up of polymers. As an embodiment, polyimide is filled with a high aspect ratio of CO2-philic Na-SSZ-39 zeolite with ultra-high loading to obtain a three-dimensional channel system for accurately separating gas molecules. By designing both zeolite and MMM synthesis, a flexible and aging-resistant (more than 1 year) membrane is obtained. The combination of CO2-CH4 mixed gas selectivity of ~423 and CO2 permeability of ~8300 Barrer is superior to all existing polymer-based membranes and even superior to most zeolite-only membranes.
[0008] The invention is further summarized in the following statement:
[0009] 1. A mixed matrix membrane (MMM) for filtration and separation of fluids obtainable by a process according to any one of statements 14 to 27, wherein the membrane comprises a glassy polymer matrix having at least 20% w / w zeolite, and wherein the zeolite polymer matrix lacks interfacial voids or wherein the voids are less than 20 nm measured at their longest dimension. These MMMs may equally be used for filtration and separation of fluids, or more generally for molecular separations.
[0010] 2. MMM according to statement 1, wherein the membrane comprises a glassy polymer matrix having at least 30, 40 or 50% w / w zeolite.
[0011] 3. The MMM according to statement 1 or 2, wherein the zeolite is a platelet-shaped, cube-shaped, cuboid-shaped, spherical-shaped or octahedral-shaped zeolite.
[0012] 4. MMM according to any one of statements 1 to 3, wherein the zeolite is in platelet shape and has a concentration in the membrane of at least 20% w / w, at least 30% w / w, at least 40% w / w, or at least 50% w / w.
[0013] 5. MMM according to any one of statements 1 to 4, wherein the membrane has a concentration of at least 40% w / w zeolite and has a CO2 permeability of at least 4000 barrer.
[0014] 6. MMM according to any one of statements 1 to 5, wherein the membrane has a concentration of at least 20% w / w zeolite / polymer and has a CO2 / CH4 selectivity of >100.
[0015] 7. MMM according to any one of statements 1 to 5, wherein the membrane has a concentration of at least 40% w / w zeolite and has a CO2 / CH4 selectivity of >400.
[0016] 8. MMM according to any one of statements 1 to 7, wherein the zeolite is in the form of plates.
[0017] 9. MMM according to any one of statements 1 to 8, wherein the zeolite is 8 or 12 membered ring.
[0018] 10. MMM according to any one of statements 1 to 9, wherein the zeolite is of AEI type.
[0019] 11. MMM according to any of statements 1 to 10, wherein the membrane is flexible and has a flexural modulus between 2 up to 9 GPa.
[0020] 12. MMM according to any of statements 1 to 11, wherein the membrane is flexible and has a flexural modulus between 3.5 and 9 MPa.
[0021] 13. MMM according to any one of statements 1 to 12, wherein the polymer is a polyimide.
[0022] 14. A method for preparing a mixed matrix membrane comprising the steps of:
[0023] a) preparing a glassy polymer and zeolite mixture in a solvent, wherein the solvent comprises at least 5% w / v polymer and comprises at least 20, 30, 40 or 50% w / w zeolite,
[0024] b) pouring the mixture obtained in step a),
[0025] c) drying the casting mixture obtained in step b) to obtain a membrane, wherein the drying is carried out at a rate of removing between 85 and 95% by weight of the solvent within a period of between 15 minutes and 24 hours,
[0026] d) heating the dried film obtained in step c) at a temperature below the glass transition temperature of the polymer, wherein the heating is maintained for a period of between 5 min and 24 hours and / or is carried out at a temperature between 30 and 300° C., provided that the temperature is below the transition temperature of the polymer.
[0027] No cross-linking of the membranes occurred during the preparation of these membranes.
[0028] Furthermore, as shown in the examples, the drying step c can be carried out with the application of a vacuum.
[0029] 15. A process according to statement 14, wherein the solution of the polymer and the dispersion of the zeolite are prepared separately and subsequently mixed.
[0030] 16. A process according to statement 14 or 15, wherein the drying in step c) is carried out at a rate such that between 85 and 95 wt % of the solvent is removed over a period of between 5 minutes and 24 hours.
[0031] 17. A process according to statement 14 or 15, wherein the drying in step c) is carried out at a rate such that between 85 and 95% by weight of the solvent is removed over a period of between 3 and 24 hours.
[0032] 18. A method according to any one of statements 14 to 17, wherein in step d, the film is heated at a temperature between 30°C and the glass transition temperature of the polymer.
[0033] 19. A method according to any one of statements 14 to 17, wherein in step d, the film is heated at a temperature between 120 or 150°C and the glass transition temperature of the polymer.
[0034] 20. The process according to any one of statements 14 to 19, wherein the heating in step d) is maintained for a period of between 4 hours and 24 hours.
[0035] 21. The process according to any one of statements 14 to 19, wherein the heating in step d) is maintained for a period of between 8 hours and 24 hours.
[0036] 22. The process according to any of statements 14 to 19, wherein the heating in step d) is maintained for a period of between 8 hours and 24 hours and / or wherein step d) is carried out at a temperature between 150°C and 300°C.
[0037] 23. A method according to any one of statements 14 to 22, followed by a step wherein the absence of voids is determined.
[0038] 24. A method according to statement 23, wherein the absence of voids is determined by microscopy.
[0039] 25. A method according to statement 23, wherein the absence of voids is determined by measuring the flow rate of the gas over the membrane.
[0040] 26. A process according to any one of statements 14 to 25, wherein the zeolite is in the form of plates.
[0041] 27. A process according to any one of statements 14 to 26, wherein the zeolite is of the AEI type.
[0042] 28. A method according to any one of statements 14 to 27, wherein the polymer is a polyimide.
[0043] A mixed matrix membrane (MMM) for filtering and separating fluids, obtainable by a method according to any one of statements 14 to 27. Detailed Description BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 :A. SEM image of sheet-shaped Na-SSZ-39 zeolite; B. SEM cross-sectional image of Na-SSZ-39MMM without thermal annealing (20 wt% zeolite loading); C. SEM cross-sectional image of Na-SSZ-39MMM after thermal annealing at 260°C (20 wt% zeolite loading); D. SEM cross-sectional image of Na-SSZ-39MMM after thermal annealing at 260°C (40 wt% zeolite loading); E. SEM cross-sectional image of 30 wt% Na-SSZ-39MMM after oxidation treatment at 800°C; F. SEM top view of membranes with 0 wt% to 50 wt% zeolite loading; G. SEM bottom view of membranes with 0 wt% to 50 wt% zeolite loading.
[0046] Figure 2Gas separation performance of Na-SSZ-39MMM membranes: A. Selectivity differences between rectangular Na-SSZ-39MMM and flake Na-SSZ-39MMM; B and C. Temperature and pressure dependence of CO2 / CH4 selectivity and CO2 permeance (from bottom to top: 0 wt%, 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt% zeolite loading); D and E. Zeolite-based MMMs from literature [squares] plotted against the 2008 CO2 / N2 and CO2 / CH4 Robeson plots, and stars represent data from MMMs with flake-shaped Na-SSZ-39 fillers (from left to right, 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 55 wt% zeolite loading); F. Pure zeolite membranes from literature [squares] compared with 50 wt% Na-SSZ-39MMM in the 2008 CO2 / CH4 Robeson plot.
[0047] Figure 3 .a CO2, CH4, and N2 adsorption isotherms of Na-SSZ-39 and SSZ-39 zeolites based on high pressure physical adsorption experiments at 10 °C. The results show high CO2 affinity and gas uptake capacity.
[0048] Figure 3 .b Comparison of experimental and GCMC simulation results of the monogas adsorption isotherms of CO2, CH4, and N2 on Na-SSZ-39 zeolite at 25 °C.
[0049] Figure 3 .c Comparison of the monogas adsorption isotherms of CO2 and CH4 and the binary gas adsorption isotherms of CO2 / CH4 (50 vol% / 50 vol%) on Na-SSZ-39 zeolite at 25°C (by GCMC simulation). CO2 adsorption prevents CH4 adsorption, indicating a strong competitive gas adsorption behavior that enhances the mixed gas separation performance.
[0050] Figure 3 .d Comparison of the monogas adsorption isotherms of CO2 and N2 and the binary gas adsorption isotherms of CO2 / N2 (50 vol% / 50 vol%) for Na-SSZ-39 zeolite at 25°C (by GCMC simulation). CO2 adsorption prevents N2 adsorption, indicating a strong competitive gas adsorption behavior that enhances the mixed gas separation performance.
[0051] Figure 3 .e 3D CO2 adsorption density map of Na-SSZ-39, CO2 adsorption isosurfaces at 0.1 bar (cross section represented by ellipse) and 1 bar (total grey cloud).
[0052] Figure 3.f Illustration of random, non-aligned packing of zeolite sheets in a polymer matrix for zeolite loadings ranging from 10 wt% to 50 wt%.
[0053] Figure 3 .g 3D illustration of the random, non-aligned packing of zeolite sheets inside a polymer matrix.
[0054] Figure 4 Cross-sectional SEM image of Na-SSZ-39MMM with a 24-hour thermal annealing schedule at 260°C, which reveals a defect-free zeolite / polymer interface and no voids are observed. This image indicates good zeolite and polymer compatibility (no membrane leakage) and predicts high membrane performance.
[0055] Figure 5 Top view SEM image of Na-SSZ-39MMMs following a thermal annealing procedure at 260 °C for 24 hours, revealing a defect-free zeolite / polymer interface with no voids observed.
[0056] Figure 6 SEM image of the cross section of Na-SSZ-39MMM after thermal annealing at 300°C for 24 hours. Separation occurred between the zeolite and the matrimid matrix.
[0057] Figure 7 Cross-sectional SEM image of Na-SSZ-39MMM after thermal annealing at 350 °C for 24 h. Further separation between the zeolite and the matrimid matrix.
[0058] Figure 8 XRD results of thermally annealed (260°C program) Na-SSZ-39MMM from 0 wt% (pure matrimid) to 55 wt% zeolite loading. The membrane samples show strong characteristic XRD signals of AEI zeolite, indicating very high zeolite loading of the membrane.
[0059] Fig. 9 Transmission FTIR patterns of Na-SSZ-39 zeolite, pristine matrimid membranes and thermally annealed (in the case of 260°C program) 0 wt% (pure matrimid membrane), 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 55 wt% Na-SSZ-39 MMM. In addition to the characteristic peaks of zeolite, no new peaks were observed after zeolite loading and heat treatment, indicating that no chemical reaction occurred in the zeolite / polymer interface.
[0060] Fig.10Comparison of mono- and equimolar binary CO2 / N2 and CO2 / CH4 gas solubility selectivities for Na-SSZ-39 zeolite based on GCMC simulation (at 25°C). The CO2 / N2 and CO2 / CH4 solubility selectivities in the binary gas case are higher than those in the mono-gas case, indicating strong competitive gas adsorption behavior that enhances the mixed gas separation performance.
[0061] Fig.11 Carbon dioxide, nitrogen and methane adsorption isotherms of thermally annealed (260°C program) neat matrimid membranes and 50 wt% Na-SSZ-39MMM at 25°C. The gas uptake performance is significantly enhanced with zeolite loading.
[0062] Fig.12 Carbon dioxide adsorption isotherms of Na-SSZ-39, SSZ-39 and Na-SSZ-39MMM for the temperature range of 10-50°C. The dotted line corresponds to the Toth isotherm model. High CO2 adsorption capacity and high CO2 affinity are exhibited, and Na-SSZ-39 shows enhanced CO2 gas uptake performance and increased CO2 affinity.
[0063] Fig.13 Methane adsorption isotherms of Na-SSZ-39, SSZ-39, and Na-SSZ-39MMM for the temperature range of 10-50°C. The dashed line corresponds to the Toth isotherm model. The CH4 adsorption capacity and CH4 affinity are significantly lower than those for CO2.
[0064] Fig.14 Nitrogen adsorption isotherms of Na-SSZ-39, SSZ-39, and Na-SSZ-39MMM for the temperature range of 10-50 °C. The dashed line corresponds to the Toth isotherm model. The N2 adsorption capacity and N2 affinity are significantly lower than the CO2 case.
[0065] Fig.15 Tensile and load force plots for 3-point bending tests of 4 membrane samples: pure Matrimid membrane (no heat treatment); pure Matrimid membrane thermally annealed at 260°C; 50 wt% zeolite MMM (no heat treatment); 50 wt% zeolite MMM thermally annealed at 260°C. All membrane samples showed good flexibility during the test, and all membrane samples returned to their original shape after the load was removed. Although both zeolite loading and thermal annealing treatment reduced the flexibility of the membrane samples, the annealed 50 wt% MMM still showed high flexibility. And the zeolite MMM with a lower zeolite loading can have higher flexibility than this membrane sample.
[0066] Fig.16DSC results of 10 wt% and 30 wt% Na-SSZ-39MMM with thermal annealing at 260° C. The glass transition temperature (Tg) of annealed Na-SSZ-39MMM increased from 320° C. to 330° C., pointing to the hardening of the polymer chains at the polymer-zeolite interface, indicating that the zeolite was encapsulated by the polymer.
[0067] Fig.17 : Robeson plot of CO2 / CH4 selectivity and permeability. Circles are values for prior art membranes. Stars refer to membranes of examples of the invention.
[0068] Fig.18 : Gas separation performance of zeolite-filled MMMs prepared by the method of the present invention:
[0069] (A) The performance of zeolite-filled MMMs from the literature is shown in the CO2-CH4 2008 Robeson diagram, and the stars represent Na-CHA-10 / Matrimid MMMs;
[0070] (B) The performance of zeolite-filled MMMs from the literature is shown in the CO2-N2 2008 Robeson diagram, and the stars represent Na-FAU-2 / Matrimid MMMs;
[0071] (C) The performance of zeolite-filled MMMs from the literature is shown in the CO2-N2 2008 Robeson diagram, and the stars refer to 50 wt% Na-FAU-2 / polysulfone MMMs and the open stars indicate unfilled polysulfone membranes.
[0072] In panels A and B, the different stars represent different zeolite loadings in the MMM. From left to right, they are 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt% zeolite.
[0073] The concentration of zeolite in the membrane can also be expressed as % w / w. Since the membrane only has zeolite and polymer, it refers to the amount of zeolite as the sum of zeolite + polymer. In this context, 20% w / w zeolite is, for example, 10 grams of membrane with 2 grams of zeolite and 8 grams of polymer (2 grams of zeolite / 2 grams of zeolite + 8 grams of membrane).
[0074] As can be derived from embodiments of the present invention, the polymers in the membranes of the present invention are not cross-linked.
[0075] Glassy polymers are a class of polymers that exhibit a high stiffness, glassy, amorphous solid state at room temperature. The glass transition temperature (Tg) of glassy polymers is above room temperature. This means that unlike rubbery polymers, glassy polymers can maintain a glassy, random arrangement of their molecular chains with high strength and stability at room temperature. Examples of glassy polymers are polystyrene, polyimide, polysulfone, polyvinyl acetate, polylactic acid, polyvinyl chloride, polymethyl methacrylate, polysulfone, poly(ether sulfone), polycarbonate, polypropylene, and polyethylene.
[0076] Mixed matrix membranes (MMMs), composed of fillers embedded in a polymer matrix, combine the inherent advantages of polymer membranes with the excellent gas separation properties of fillers.
[0077] Zeolites are particularly interesting for MMM development because they have well-defined, rigid pores and outstanding thermal and chemical stability. Because the inherent low selectivity and high permeability of rubbery polymers (such as polydimethylsiloxane) offset the benefits of zeolites, rigid glassy polymers are used to develop high-performance zeolite-filled MMMs. However, poor adhesion between zeolite and glassy polymers typically results in non-selective interface voids. Therefore, it is necessary to obtain high zeolite loading (≥50 wt %), while ensuring defect-free polymer-zeolite interface, combining high-selectivity zeolites and appropriate glassy polymer matrix to produce high-performance MMMs for various most critical separation challenges. As an example, sheet shape, CO2, small pore (eight-membered ring) AEI type zeolite (SSZ-39) (possessing long-range ordered three-dimensional (3D) channel system and gas selectivity window) is incorporated into poly (3,3′-4,4′-benzophenone tetracarboxylic acid-dianhydride diaminophenyl indane) (Matrimid 5218) polymer. The combination of zeolite and MMM synthesis results in high zeolite loading with a quasi-continuous zeolite phase across a self-standing membrane.
[0078] A first aspect of the invention relates to a mixed matrix membrane (MMM) for filtration and separation of gases, said membrane comprising a glassy polymer matrix having at least 20 or 30% w / w (zeolite / (zeolite+polymer)).
[0079] Instead of filtering and separating gases, the membranes can be used for other types of molecular filtration.
[0080] The membrane may be further characterized by the zeolite polymer matrix lacking interfacial voids or voids measuring less than 50 nm, less than 20 nm, or less than 10 nm in their longest dimension.
[0081] In these membrane embodiments, the zeolite is a platelet-shaped, cube-shaped, cuboid-shaped, spherical-shaped, or octahedral-shaped zeolite.
[0082] Other examples of suitable and commercially available zeolites for use in the membranes of the present invention are cubic shaped CHA, spherical shaped LTA, octahedral shaped FAU.
[0083] Based on SEM images (with 10000-25000 magnification) of the membranes of the present invention of top, bottom and cross-sectional views of the membranes, no detectable (less than 20 nm) voids were observed. This was confirmed by the gas separation results using these membranes. Ultra-high selectivity membranes were obtained (gas selectivity > 420 for a CO2 / CH4 mixed gas feed stream). In this case, a small leak through the voids will cause a significant loss of selectivity.
[0084] As an alternative to defining the properties of a membrane by permeability or selectivity, the membrane can also be characterized with reference to the Robeson upper limit which describes the performance trade-off between permeability and selectivity. This is a limit beyond which no prior art membrane shows performance for a given separation (e.g. CO2 / N2 or CO2 / CH4). The Robeson relationship between selectivity α and permeability P (in Barr units) can be expressed as:
[0085] α.P n =k
[0086] Where n and k are coefficients. Because the selectivity and permeability of membranes are typically plotted on a logarithmic scale, the Robeson plot is linear in shape. The area above the Robeson plot can be expressed as:
[0087] α.P n >k
[0088] For CO2 / CH4 gas separation by prior art mixed matrix membranes, the Robeson upper limit can be expressed as aP 0.41 = 550. The current working Na-AEI mixed matrix membranes show aP ranging from 660-20,000 0.41 values and zeolite concentration values between 20 and 55%, i.e. much greater than 550 (cf. Fig.17 ).
[0089] For CO2 / N2 separation by prior art mixed matrix membranes, the Robeson upper limit can be expressed as aP 0.34 =250.
[0090] For CH4 / N2 separation by prior art mixed matrix membranes, the Robeson upper limit can be expressed as aP 0.239 =6.79. In this work, 65 wt% Na-CHA MMM is shown to have aP much greater than 6.79 and in the range of up to 50-60 0.239 value.
[0091] In an embodiment of the first aspect of the invention, the zeolite is in the form of flakes and has a concentration in the polymer of at least 10% w / w, at least 15% w / w, at least 20% w / w, at least 25% w / w, at least 30% w / w, at least 40% w / w, or at least 50% w / w (zeolite / polymer).
[0092] Note that a concentration of 30% w / w platelet-shaped zeolite corresponds to 25 v / v% of the volume of zeolite in the membrane.
[0093] In an embodiment of the first aspect of the invention, the zeolite is cubic in shape and has a concentration in the polymer of at least 30% w / w, at least 40% w / w, at least 50% w / w, or at least 60% w / w (zeolite / polymer).
[0094] In an embodiment of the first aspect of the invention, a membrane having a zeolite / polymer concentration of at least 30% w / w has a CO2 permeability of at least 600 barrer.
[0095] In an embodiment of the first aspect of the invention, a membrane having a zeolite / polymer concentration of at least 40% w / w has a CO2 permeability of at least 4000 barrer.
[0096] In an embodiment of the first aspect of the invention, a membrane having a zeolite / polymer concentration of at least 50% w / w has a CO2 permeability of at least 10,000 barrer.
[0097] In an embodiment of the first aspect of the invention, a membrane having a zeolite / polymer concentration of at least 20% w / w has a CO2 / CH4 selectivity of >100.
[0098] In an embodiment of the first aspect of the invention, a membrane having a zeolite concentration of at least 30% w / w has a CO2 / CH4 selectivity of >300.
[0099] In an embodiment of the first aspect of the invention, a membrane having a zeolite concentration of at least 40% w / w has a CO2 / CH4 selectivity of >400.
[0100] In an embodiment of the first aspect of the invention, the zeolite is in the form of flakes.
[0101] In an embodiment of the first aspect of the invention, the zeolite is in a random non-aligned packing within the polymer.
[0102] In an embodiment of the first aspect of the invention the zeolite is an 8, 10 or 12 membered ring.
[0103] Other suitable zeolites for use in the inventive membranes are zeolites such as RRO, RHO, FER and LTA.
[0104] In an embodiment of the first aspect of the invention the zeolite is of the AEI, CHA, LTA or FAU type.
[0105] Herein CHA is cube-shaped, LTA is spherical and FAU is octahedral.
[0106] It is clear that CHA, LTA and FAU can also be prepared as defect-free zeolites MMM for gas separations.
[0107] In an embodiment of the first aspect of the invention the zeolite is of the AEI type.
[0108] In an embodiment of the first aspect of the invention, the AEI framework contains no extra-framework aluminum species.
[0109] In an embodiment of the first aspect of the invention, the zeolite is a platelet-shaped, 8-membered AEI type SSZ-39 zeolite.
[0110] Changes in the zeolite framework type result in different pore sizes and have an impact on the type of gas to be separated. Likewise, the type of counter cation affects the interaction with the gas molecules and thus affects the selectivity and pore size. The Si / Al molar ratio also affects the polarizability and pore size.
[0111] Approximately 10% of the aluminum sites of SSZ-39 zeolite are occupied by Na+ and at least 90% of the aluminum sites of Na-SSZ-39 (fully Na+ exchanged SSZ-39 zeolite) are occupied by Na+.
[0112] In an embodiment of the first aspect of the invention at least 40%, at least 60%, at least 80%, at least 95%, at least 98% or at least 99% of the aluminium sites in the zeolite are occupied by sodium ions.
[0113] The addition of aluminum sites allows for tuning of the polarizability and counterions of the zeolite filler, which will alter the gas adsorption / diffusion properties and affect overall membrane performance.
[0114] The data of the present invention reveal that the gas separation performance of zeolite MMM is strongly dependent on the Si / Al molar ratio of the zeolite filler.
[0115] In an embodiment of the first aspect of the invention, the platy zeolite has a thickness between 90 and 200 nm.
[0116] In an embodiment of the first aspect of the invention, the cubic or cubic, cuboid, spherical or octahedral zeolite has a particle size between 200 nm and 5 μm.
[0117] In an embodiment of the first aspect of the invention, the platelet-shaped zeolite has a size between 1 x 1 μm or 1.25 x 1.25 μm and between 1.75 x 1.75 μm or 2 x 2 μm.
[0118] In an embodiment of the first aspect of the invention the zeolite has a bulk density of between 15, 20 or 50 mg / cm3 up to 100, 200, 500 mg / cm3.
[0119] In an embodiment of the first aspect of the invention the film is flexible and has a flexural modulus of between 3.5, 4, or 4.5, up to 6.0, 6.5, 7, 7.5, 8.0, 8.5 up to 9 MPa.
[0120] In an embodiment of the first aspect of the invention, wherein the polymer is a polyimide. Glassy polymers typically used in the present invention have lower gas permeabilities than the zeolite filler. The polymer is compatible with the zeolite filler and can surround the zeolite filler but does not invade the pores. The polymer does not decompose during thermal annealing and does not shrink by more than >10 volume %.
[0121] A second aspect of the invention relates to a method for preparing a mixed matrix membrane comprising the following steps:
[0122] -a) dissolving the glassy polymer in a solvent,
[0123] -b) preparing a zeolite dispersion [typically in the solvent of step a]
[0124] -c) mixing the dissolved polymer of a) with the dispersion of b) in such an amount that the mixture comprises at least 5% w / v polymer / solvent and the amount of zeolite is at least 20, 30, 40 or 50% w / w zeolite / (zeolite+polymer),
[0125] -d) pouring the mixture obtained in step c),
[0126] -e) drying the mixture to obtain a film,
[0127] -f) heating the film obtained in step e) at a temperature between 120 or 150° C. and the glass transition temperature of the polymer,
[0128] Typically an upper limit of 15-20 wt% polymer / solvent can be used in step c).
[0129] Specific embodiments of the process use a type of zeolite in a concentration to obtain MMM (as described in the above aspects for the MMM product).
[0130] As can be appreciated from the Examples section, the method does not involve or require cross-linking of the polymer in the membrane.
[0131] In an embodiment of the second aspect of the invention, the drying in step e) is carried out at a rate to remove between 85 and 95 wt % of the solvent over a period of between 3 and 24 hours.
[0132] In such a process, the rate of solvent removal is monitored to prevent separation of the hardened polymer of the zeolite.
[0133] In an embodiment of the first aspect of the invention, heating is maintained for a period of between 8 hours and 24 hours.
[0134] In embodiments of these methods, a funnel is used to create a confined space above the casting solution film to reduce the rate of solvent removal.
[0135] For example, chloroform has a boiling point of 61.2°C, so a funnel is used to slow down the rate of solvent evaporation.
[0136] In other embodiments, high boiling point (typically greater than 150°C) solvents (eg, Tamisolve, boiling point -240°C) or a climate chamber with a solvent vapor atmosphere are used to reduce the solvent evaporation rate.
[0137] In an embodiment of the second aspect of the invention, it is carried out at a temperature between 150°C and 300°C.
[0138] In an embodiment of the first aspect of the invention, step f is carried out at a temperature between 180°C and 280°C, or between 200 and 280°C, or between 240 and 280°C, or between 250 and 270°C.
[0139] In an embodiment of the second aspect of the invention, the method further comprises the steps of determining the gas permeability and selectivity of the prepared membrane and selecting a membrane having a permeability at least 100% higher and a CO2 / CH4 selectivity at least 50% higher than that of the same membrane without zeolite subjected to the same heat treatment.
[0140] In an embodiment of the second aspect of the invention, the zeolite is in the form of flakes.
[0141] In an embodiment of the second aspect of the invention, the zeolite is an 8-membered ring.
[0142] In an embodiment of the second aspect of the invention, wherein the zeolite is of AEI type.
[0143] In an embodiment of the second aspect of the invention, the polymer is a polyimide.
[0144] In an embodiment of the second aspect of the invention, the solvent is chloroform or a dipolar aprotic solvent.
[0145] A third aspect of the invention relates to a membrane obtainable by the method disclosed above as the second aspect of the invention and embodiments thereof.
[0146] The gas separation performance of the MMMs of the present invention can be explained by a number of factors.
[0147] Zeolites possess enormous diffusivity and solubility selectivity, thus facilitating ultrahigh mixed gas selectivity. In specific embodiments, the non-centrosymmetric AEI-type framework allows for the preparation of high aspect ratio sheets.
[0148] In addition, the sudden jump in the CO2-CH4 separation coefficient with increasing zeolite % loading indicates a percolation effect, whereby gas permeation through the membrane is primarily through the zeolite phase. The zeolite creates a quasi-continuous zeolite phase across the membrane that allows percolation of gas molecules while minimally affecting the less permeable polymer phase. Zeolite sheets accumulate from the bottom up and appear at the top of the membrane. The non-aligned, randomly oriented distribution results in a selective gas permeation highway, allowing for the performance of the membrane. It was further discovered that sheet-shaped zeolites result in better selectivity and permeability than cuboid-shaped zeolites.
[0149] Furthermore, the overall gas transport through the MMM is the net result of the properties of both the zeolite and the polymer and their interaction with each other, thus it is important to obtain a defect-free zeolite-polymer interface. Although rubbery polymers such as polydimethylsiloxane (PDMS) promote the creation of a defect-free interface, their inherent low selectivity and high permeability offset the beneficial contribution of the zeolite embedded therein. The membrane preparation method of the present invention prevents the occurrence of non-selective voids at the zeolite-polymer interface, allowing ultra-high zeolite loadings of >50 wt% without chemical modification of the zeolite or polymer and without the use of additives.
[0150] Ultra-high performance zeolite-filled MMMs for CO2 separation have been developed, which show unprecedented CO2 removal performance, not only greater than the CO2 removal performance of any existing polymer membrane or MMM, but even exceeding the CO2 removal performance of most zeolite-only membranes. By avoiding the traditional incompatibility between zeolite fillers and glassy polymer matrices, flexible, defect-free zeolite-polyimide MMMs with ultra-high (>50 wt%) zeolite loadings were prepared. Na-SSZ-39 zeolite was found to be an excellent filler because of its outstanding affinity for CO2, precise molecular sieve window, strong competitive adsorption behavior and excellent stability, thereby promoting strong, non-aging CO2 separation performance. Due to the high aspect ratio and 3D channel system of the filler, a percolation gas permeation highway is generated across the membrane, thus significantly enhancing the performance of the membrane.
[0151] The use of a scalable process to prepare defect-free zeolite-filled membranes with commercially available glassy polymers thus opens the door to the development of processable, robust and economical high-performance zeolite-filled MMMs for a variety of gas and liquid separations. This is particularly beneficial for those zeolites that are difficult to process into defect-free, zeolite-only membranes.
[0152] Example 1 Laboratory-scale mixed matrix membrane preparation
[0153] Prepare mixed matrix membranes (MMM) containing 10, 20, 30, 40, 50, 55 wt % of zeolite. First, 0.3 g of Matrimid was dissolved in 2.70 g of chloroform to prepare a 10 wt % uniform Matrimid solution. Next, a certain amount of zeolite was added to 1.80 g of chloroform to prepare a zeolite dispersion. The zeolite dispersion was stirred for 2 h and thoroughly sonicated for 1 h. For each zeolite dispersion, 3 g of 10 wt % Matrimid solution was added. All zeolite / polymer solutions were stirred for 8 h on a magnetic stirring plate and sonicated twice (1 hour per round) at the beginning and end of the stirring process. The final mixture was poured into a Petri dish (d=7 cm) in a nitrogen bag. The polymer concentration was adjusted to about 7 wt % to obtain a viscous solution that can be poured but will not suffer too much zeolite precipitation during solvent evaporation. The mixture was then poured into a glass funnel (diameter=3 mm, the internal volume of the funnel ≈30 cm) with a small opening. 3 ) was placed above the Petri dish to slow down the evaporation of chloroform. The glass funnel produced a saturated chloroform vapor phase above the polymer solution layer, thereby reducing the solvent evaporation rate. This resulted in the film slowly solidifying in about 1 hour. The solidified film was kept in a nitrogen bag for 12 hours, removed from the Petri dish and dried naturally for 10 hours before heat treatment. The zeolite loading was calculated by using equation 1:
[0154]
[0155] Where m 沸石 and m 聚合物 are the weights of zeolite and polymer, respectively.
[0156] For the post-heat annealing process, the dried film was placed between glass supports to prevent curling and placed in a muffle furnace. The muffle furnace was heated to 180°C, 260°C (below the glass transition temperature (Tg) of Matrimid), 300°C (below but close to the Tg of Matrimid), and 350°C (above the Tg of Matrimid). The heating regimen required a 1°C min -1The final annealing temperature was heated from room temperature in increments of 30°C. The furnace was kept isothermal for 2 hours at each increment. The membrane was kept at the final temperature for 24 hours and removed after the furnace cooled naturally to room temperature, because too rapid quenching would create voids between the polymer matrix and the filler (due to the difference in thermal expansion coefficients of the two materials). By allowing the MMM to cool naturally, good adhesion between the polymer chains and the zeolite can be maintained.
[0157] Example 2 Zeolite Characterization
[0158] Powder X-ray diffraction (pXRD) of Na-SSZ-39 zeolite confirmed a highly crystalline AEI framework, which is very consistent with previous studies of Na-SSZ-39. N2 adsorption experiments showed that the synthesized Na-SSZ-39 has a nearly 100% micropore content and a pore size of 0.28-0.29 cm 3 / g pore volume, which is close to the theoretical maximum accessible volume of the AEI type framework. According to the literature, Na-SSZ-39 synthesis leads to an AEI framework without extra-framework aluminum species, which indicates a nearly perfect, 3D connected channel system, allowing fast gas transport. SEM images show a thickness of ~100nm and a size of approximately 1.5×1.5μm 2 The flake-shaped Na-SSZ-39 zeolite ( Figure 1 .a). Due to the loose packing of zeolite sheets, 20 mg / cm 3 Very low bulk density.
[0159] For SSZ-39 zeolite (SSZ-39, Na / Al ratio = 0.12) and Na + -Exchanged SSZ-39 (Na-SSZ-39, Na / Al ratio = 0.93) zeolite for determination of CO2, CH4 and N2 gas uptake and isovolumetric adsorption enthalpy (Q st ). Fig.12 , 13 , 14 show the adsorption isotherms of CO2, CH4 and N2 at 10°C to 50°C in the pressure range of 0-8 bar. For both SSZ-39 and Na-SSZ-39, the gas uptake decreases in the logical order of CO2>CH4>N2, which is attributed to the expected differences in polarizability and quadrupole moment of the adsorbate. The maximum CO2 uptake of Na-SSZ-39 at 10°C reaches 10.87 mmol / cm 3 (253.1cm 3 (STP) / cm 3 ), while SSZ-39 showed uptake of 10.66mmol / cm 3 (248.2cm 3 (STP) / cm 3To further quantify the CO2 affinity of Na-SSZ-39, the Toth model was used to determine the CO2 Q under zero coverage. st =-35.1 kJ / mol. Due to the large polarizability and quadrupole moment of CO2, the adsorption heat of CO2 in Na-SSZ39 (-35.1 kJ / mol) is much greater than that of CH4 (-21.4 kJ / mol) and N2 (-19.4 kJ / mol) (Table 1). Overall, it can be observed that Na-SSZ-39 obtains a more negative CO2 adsorption enthalpy and a higher CO2 uptake compared with SSZ-39. In addition, the significant difference in CO2 adsorption in the low-pressure region of the isotherm indicates that Na + The exchange results in an increased affinity of the zeolite for CO2.
[0160] Table 1 Fitted Toth parameters (with 95% confidence intervals) for CO2, CH4 and N2 adsorption isotherms of three samples (Na-SSZ-39, SSZ-39, 50 wt% Na-SSZ-39MMM).
[0161]
[0162] To further explain the experimental findings at the molecular level, the pure gas and mixed gas adsorption behaviors in Na-SSZ-39 were modeled using Grand Canonical Monte Carlo (GCMC) simulations. The results from the pure gas adsorption simulations showed good qualitative similarity to the experimental data ( Figure 3 .b), and the adsorption enthalpies are also consistent (GCMC at 2 bar yields -31.6 kJ / mol for CO2, -18.5 kJ / mol for CH4, and -15.8 kJ / mol for N2). From the 3D density isosurfaces of CO2 adsorption ( Figure 3 .e) It can be seen that CO2 molecules preferentially bind to Na + interaction (especially at low CO2 pressures), while the window of Na-SSZ-39 remains open for gas transport. + This trend at the site confirms that Na + The CO2 affinity of the zeolite was enhanced after the exchange, which improved the CO2 adsorption in Na-SSZ-39. In addition, the CO2 / CH4 mixed gas adsorption simulation on Na-SSZ-39 clearly showed that the competitive adsorption of CO2 at the expense of CH4 significantly reduced the CH4 uptake ( Figure 3 .c). Compared with the single gas adsorption results ( Figure 3 Compared with a), at 5 bar and 25 °C, the CH4 uptake under mixed gas conditions decreased from 1.94 mmol / g to 0.26 mmol / g ( Figure 3.c). In addition, the ab initio free energy barrier calculation of the diffusion inside the zeolite further confirmed the molecular sieve behavior of Na-SSZ-39 zeolite. (This is close to the kinetic diameter of a CH4 gas molecule And it is significantly larger than the kinetic diameter of CO2 ), so the free energy barrier for CH4 to permeate through the 8-membered ring in Na-SSZ-39 is about twice as high as that for CO2. Therefore, the self-diffusion coefficient of CO2 is more than three orders of magnitude higher than that of CH4.
[0163] The pure gas and mixed gas adsorption behaviors in SSZ-39 were modeled by Grand Canonical Monte Carlo (GCMC) simulations. The results from the pure gas adsorption simulations showed good agreement with the experimental data ( Figure 3 .b). In addition, the 3D density map of CO2 adsorption ( Figure 3 .e) It shows that CO2 adsorption mainly occurs in the zeolite cage, and CO2 preferentially reacts with Na + interaction (especially at low CO2 pressures), while the window of Na-SSZ-39 remains open for gas transport. CO2 molecules tend to approach Na + site, which explains the Na + The CO2 affinity of the zeolite after exchange was enhanced, which improved the CO2 adsorption on Na-SSZ-39. More importantly, the CO2 / CH4 mixed gas adsorption simulation on Na-SSZ-39 clearly showed that the competitive adsorption of CO2 at the expense of CH4 significantly reduced the CH4 uptake ( Figure 3 .c). Compared with the single gas adsorption results, under mixed gas conditions at 5 bar and 25 °C, CH4 uptake increased from 72.3 cm 3 STP / cm 3 Down to 7.9cm 3 STP / cm 3 In addition, the calculation of the energy barrier for diffusion inside the zeolite further confirms the molecular sieve behavior of Na-SSZ-39 zeolite. Because the maximum pore size of Na-SSZ-39 zeolite is Close to the kinetic diameter of CH4 gas molecules Therefore, the energy barrier for CH4 permeation through its pores is calculated to be twice as high as that for CO2.
[0164] Example 3 MMM Characterization
[0165] MMMs were prepared with Na-SSZ-39 to achieve loadings as high as a truly outstanding 55 wt%. XRD confirmed the retention of zeolite crystallinity in the MMMs after heat treatment ( Figure 8). SEM cross-sectional image of the membrane ( Figure 1 .d) shows that the zeolite sheets are located in a random, non-aligned packing manner in the polymer matrix. This random distribution of SSZ-39 zeolite sheets in the MMMs results from the subtle and carefully optimized interaction between the zeolite and solvent properties during the MMM synthesis process. More specifically, due to the good interaction between the Na-SSZ-39 sheets and the solvent, the small difference between the zeolite and solvent densities (1.55 g / cm 3 and 1.49 g / cm 3 , preventing particle sedimentation), high aspect ratio of the sheet-shaped zeolites and high viscosity of the final casting solution, an optimized dispersion of the zeolites in the casting solvent (i.e., chloroform) was obtained. In addition, in order to prevent the hardened polymer chains from detaching from the zeolite surface during the solvent evaporation process, the chloroform evaporation rate during the membrane formation process was slowed down. After drying the cast membrane, further interfacial defect elimination was carried out by an annealing scheme, which had a profound impact on the final MMM morphology. Several thermal annealing procedures were tested at 180°C, 260°C, 300°C and 350°C. Among them, annealing at 180°C and 260°C resulted in similar MMM CO2 permeabilities, but the 260°C procedure led to an almost doubling of the CO2 / CH4 separation factor (for 50 wt% Na-SSZ-39MMM, the separation factor increased from ~200 to >420). Annealing at temperatures above 300°C resulted in brittle and embrittled carbonized membranes, in which there were a large number of voids at the zeolite-polymer interface ( Figure 6 and Figure 7 ).
[0166] Complete removal of the polymer by oxidation treatment at 800 °C resulted in a very stable zeolite-only membrane ( Figure 1 .e), clearly demonstrating the very high zeolite loading of the random packing and the quasi-connected, continuous zeolite phase within the MMMs. Figure 1 c clearly shows that the membrane subjected to 260°C annealing treatment does not show the sieve-in-a-cage morphology, which is traditionally the main problem of zeolite MMM ( Figure 1 .b). When compared with their unannealed counterparts ( Figure 1 .b) Compared to , much better zeolite-polymer adhesion can be observed after annealing.
[0167] FTIR at a specific wave number (1050cm -1 and 1090cm -1 ), but no conclusive evidence for covalent interactions between polymer and zeolite at the interface after annealing could be found even at high zeolite loadings ( Fig. 9). To investigate the zeolite-polymer interfacial interaction in more depth, confocal Raman spectroscopy was applied, which confirmed the absence of chemical reaction between the zeolite and the polyimide. Although no signs of covalent bond formation were detected, polymer chain rearrangement and improved wrapping around the zeolite particles caused by thermal annealing could be observed. The glass transition temperature (T) of the thermally annealed Na-SSZ-39MMM increased with increasing zeolite loading from 10 wt% to 30 wt%. g ) increases steadily from 320 °C to 330 °C, pointing to the hardening of the polymer chains at the polymer-zeolite interface ( Fig.16 ), indicating that the zeolite is encapsulated by the polymer, thus restricting the thermal motion of the polymer and requiring more energy for polymer chain motion. CO2, CH4 and N2 adsorption experiments were performed on pristine Matrimid membranes annealed at 260°C and 50 wt% Na-SSZ-39MMM to quantify their respective gas uptakes. When compared to pure Matrimid membranes, MMM showed significantly higher CO2, CH4 and N2 uptakes ( Fig.11 ).
[0168] Example 4 Membrane Gas Separation Performance
[0169] Benefiting from its competitive gas adsorption behavior, the mixed gas selectivity of SSZ-39MMM is significantly higher than its ideal gas selectivity (Table 2).
[0170] Table 2. CO2 / CH4 and CO2 / N2 mixed gas selectivities of Na-SSZ-39MMM at 25°C (for equimolar CO2 / N2 gas mixtures and equimolar CO2 / CH4 gas mixtures, the partial pressure of CO2, CH4, and N2 in the gas mixture is 1 bar) and CO2 / CH4 and CO2 / N2 ideal gas selectivities (the pressure of the CO2, CH4, and N2 feed streams is 1 bar).
[0171]
[0172] For example, for 50 wt% Na-SSZ-39MMM, at 1 bar / 25°C, the CO2 / CH4 ideal gas selectivity is ~335, while at 2 bar / 25°C, the CO2 / CH4 mixed gas (CO2 / CH4=50 volume% / 50 volume%) selectivity reaches ~423 (CO2 and CH4 partial pressures are both equal to 1 bar). Similarly, at 1 bar / 25°C, the CO2 / N2 ideal gas selectivity is ~32, while at 2 bar / 25°C, its mixed gas selectivity increases to ~60. Therefore, it is obvious that once the more strongly adsorbed CO2 occupies the adsorption site, the zeolite channel will be partially inaccessible to other gases and prevent the permeation of CH4 and N2. Based on MMM adsorption and pure gas permeation experiments, the gas solubility and gas diffusivity values of the original Matrimid membrane and 50 wt% Na-SSZ-39MMM were calculated (Table 3).
[0173] Table 3. Monocyclic CO2, CH4, N2 gas uptake (cm3 STP / cm3), ideal permeability P (Baler), solubility S (10 + cm 3 (STP) / cm 3 cmHg), diffusion rate D(10 8 cm2 / s), and comparison of these values for 50 wt% Na-SSZ-39MMM and pristine Matrimid membranes at 25°C and 1 bar (both membranes were subjected to a 260°C thermal annealing procedure).
[0174]
[0175] Relative to the unfilled polymer membrane, MMM showed a 4.6-fold higher CO2 solubility and the CH4 and N2 solubilities of Na-SSZ-39MMM increased by 7.5-fold and 3.4-fold, respectively. Compared to the unfilled Matrimid membrane, the CO2 diffusivity of Na-SSZ-39MMM showed a 220-fold increase, while the CH4 and N2 diffusivities increased by 14-fold and 148-fold, respectively. Therefore, the enhancement of the MMM CO2 / CH4 diffusion selectivity (+1104%) appears to be the basis for the significant improvement in the gas separation capabilities of the MMM. This can be explained by the sharp size sieving effect of Na-SSZ-39 on CH4, since the zeolite pore size Almost equal to the kinetic diameter of CH4 Because N2 has a smaller kinetic diameter Therefore, the increase in CO2 / N2 diffusion selectivity is much less significant, which is consistent with the observed CO2 / N2 permeation behavior of SSZ-39MMM. Figure 2 .D and Figure 2.E is presented. For CO2 / CH4, a continuous increase in separation factor was observed when a higher loading of Na-SSZ-39 was achieved. Whereas the unfilled Matrimid membrane showed a CO2 / CH4 separation factor of ~45 and a CO2 permeability of ~8 barrer, the best MMM performance was obtained using a 50 wt% Na-SSZ-39 loading, which obtained an amazing separation factor of ~423 at 2 bar / 25°C. At the same time, a CO2 permeability of ~8280 barrer (~1037 times increase) was obtained. Similar results were obtained for MMMCO2 / N2 separation performance. In this article, 50 wt% MMM combines a CO2 permeability of ~8300 barrer with a CO2 / N2 separation factor of ~60. Figure 2 .b and Figure 2 .c shows the temperature and pressure dependence of the CO2 / CH4 separation coefficient and CO2 permeability of Na-SSZ-39MMM with different zeolite loadings. As the temperature increases, the CO2 adsorption in the zeolite decreases ( Fig.12 ), resulting in a decrease in CO2 permeability, while CH4 permeability slightly increased, resulting in a decrease in CO2 / CH4 selectivity. Similar behavior was observed with increasing feed pressure: both CO2 permeability and CO2 / CH4 selectivity decreased. This can be explained by the high affinity for CO2 of the Na-SSZ-39 zeolite filler, which is already saturated with CO2 molecules at low feed pressures ( Fig.12 ). Therefore, further increasing the pressure has much less effect on CH4 permeability than CO2 permeability. For the same reason, when the membrane is exposed to a feed with a reduced CO2 partial pressure, Na-SSZ-39MMM exhibits enhanced performance compared to testing at an equimolar gas mixture. For example, for a 20 vol% CO2 / 80 vol% CH4 feed, 50 wt% Na-SSZ-39MMM produces a CO2 permeability of over 10,000 barrers and a CO2 / CH4 separation factor of over 460.
[0176] When plotted on a selectivity-permeability tradeoff diagram, Na-SSZ-39MMM has exceeded the tradeoff line for CO2 / CH4 ( Figure 2 .E) Starting with only 20 wt% zeolite loading and for CO2 / N2 ( Figure 2 .D) starting from 30 wt% zeolite loading. Eventually, an unprecedented jump towards the upper right corner of the Robeson diagram of the MMM is achieved, and finally even beyond the performance region dominated by pure zeolite membranes ( Figure 2.F). The outperformance over pure zeolite membranes can be related to the excellent properties of the Na-SSZ-39 filler and the unique morphology of the ultra-high zeolite loading membranes. In addition, the Na-SSZ-39MMMs additionally retain their flexibility due to the presence of the polymer matrix compared to pure zeolite membranes, indicating better scale-up potential. From an application point of view, the outstanding combination of very high flux and selectivity can allow a significant reduction in both operating and capital costs, since simplified and more energy-efficient operating schemes (which have less recirculation and milder (re) compression stages combined with reduced membrane area) can be applied.
[0177] The outstanding and outstanding gas separation performance of Na-SSZ-39MMM can be explained by a combination of factors. + The exchanged SSZ-39 zeolite creates a more CO2-philic adsorption environment, resulting in higher CO2 uptake and stronger CO2 affinity. GCMC modeling and calculation of the gas diffusion selectivity of the membrane revealed a very accurate CO2 / CH4 size sieving effect combined with a strong competitive adsorption of CO2 at the expense of CH4 and N2. This effect was confirmed by mixed gas GCMC simulations ( Figure 3 .C and Figure 3 .D) is clearly demonstrated. In other words, under mixed gas conditions, CH4 is prevented from entering the zeolite cage by a combination of geometrical restrictions of the zeolite pores and the competitive advantage of CO2 adsorption on the zeolite, further limiting the entry of CH4. The significant difference in the separation coefficients for CO2 / CH4 and CO2 / N2 (~423 and ~60, respectively, for 50 wt% Na-SSZ-39MMM at 2 bar and 25°C) is almost a direct result of the smaller kinetic diameter of N2 compared to CH4, and thus confirms the central role of the size sieving mechanism.
[0178] Second, the sudden jump of CO2 / CH4 separation coefficient under 20-30 wt% loading indicates the percolation effect, that is, from this loading, the gas permeation through the membrane is mainly determined by the zeolite phase. The reason for the offset of this phase advantage should be sought in the actual ability of introducing the zeolite of abnormally high loading in the polymer matrix. This produces a unique membrane morphology, which consists of a quasi-connected, continuous zeolite phase in the polymer matrix starting under 20-30 wt% zeolite loading, and allows the percolation of gas molecules, while minimally affecting the polymer phase. SEM top view of membranes with different zeolite loadings ( Figure 1 .E) and bottom view ( Figure 1 .F) shows that when the zeolite loading reaches 30 wt%, the zeolite sheets are stacked upward from the bottom and appear on the top of the membrane.
[0179] In this context, the non-aligned, random Na-SSZ-39 sheet distribution in the MMM polymer matrix (due to the zeolite shape and optimized MMM synthesis) is considered to be a key driver and prerequisite for the extraordinary performance of the membranes. The random zeolite packing ensures total connectivity between zeolite particles, which dictates the permeation paths for gas molecules. This is confirmed by comparing the CO2 / CH4 separation performance of MMMs containing sheet-shaped Na-SSZ-39 and MMMs carrying cuboid Na-SSZ-39. As can be seen in Figure 2 As can be seen from Figure .A, a sudden increase in CO2 / CH4 selectivity is observed only for the plate-shaped zeolite, but not for the rectangular Na-SSZ-39. In addition, the plate-shaped Na-SSZ39 MMM shows much better CO2 / CH4 selectivity and CO2 permeance than the rectangular Na-SSZ-39 MMM with the same zeolite loading.
[0180] Third, because the overall gas transport through the MMM is the net result of the properties of both the zeolite and the polymer and their interaction with each other, it is critical to obtain a defect-free interface between the Matrimid and Na-SSZ-39. The thermal annealing protocol minimizes the appearance of non-selective voids at the zeolite polymer interface, allowing ultra-high zeolite loadings of over 50 wt% without chemical modification of the zeolite or polymer nor the use of additives. This is visualized by SEM cross-sectional images.
[0181] Example 5. 3-point bending test
[0182] A 3-point bending test was performed on an Ins tron 5943 for flexural modulus measurement. The support spacing was 20 mm, and the maximum stretching distance was set to 10 mm. Four samples were tested: pure Matrimid membrane (no heat treatment); pure Matrimid membrane annealed at 260°C; 50 wt% zeolite MMM (no heat treatment); 50 wt% zeolite MMM annealed at 260°C. All membrane specimens were prepared in 60 mm × 20 mm size (thickness 80-100 μm), and each membrane specimen was tested 4 times under maximum load stretching. The flexural modulus was calculated based on Equation 1:
[0183]
[0184] w: width of the film sample;
[0185] h: thickness of the film sample;
[0186] L: distance between support spacing;
[0187] d: tensile load;
[0188] F: Load force applied at the middle of the beam.
[0189] The flexural modulus of the four membrane samples are listed in Table 1. All membrane samples did not break during the test, and all membrane samples could return to their original shape after the load was removed. As shown in the flexural modulus, both the zeolite loading and the thermal annealing treatment reduced the flexibility of the membrane samples, which increased their flexural modulus.
[0190] Table 4. Flexural modulus of film specimens.
[0191] Film name Flexural modulus(GPa) Matrimid 3.193±0.018 Annealed Matrimid 3.969±0.025 50 wt% MMM 5.86±0.226 Annealed 50 wt% MMM 6.911±0.045
[0192] Example 6. Additional embodiments of mixed matrix membranes
[0193] Prepare 3 additional membranes
[0194] -Na-CHA-10 zeolite and polyimide polymer
[0195] -Na-FAU-2 zeolite and polyimide polymer
[0196] -Na-FAU-2 zeolite and polysulfone ( S2010) polymer
[0197] Na-CHA-10 herein is a cubic shaped, 8-membered ring (8MR) CHA type framework zeolite filler with Na+ counterions and a Si / Al molar ratio of -10.
[0198] In this context, FAU is an octahedral shaped, 12-membered ring (12MR) FAU type framework zeolite filler with Na+ counterions and a Si / Al molar ratio of ~2.
[0199] These additional films were prepared using the same solvents and conditions as disclosed in Example 1, except for the final heating step.
[0200] Na-CHA-10 / Matrimid MMM and Na-FAU-2 / Matrimid MMM were then heated at 260°C for 24 hours.
[0201] The Na-FAU-2 / polysulfone MMM was then heated at 50°C for 12 hours.
[0202] Fig.18 The permeability and selectivity of these membranes compared to prior art membranes are shown, indicating similar superior properties compared to the prior art.
Claims
1. A mixed matrix membrane (MMM) for filtration and separation of gases obtainable by a process according to any one of claims 14 to 27, wherein the membrane comprises a glassy polymer matrix having at least 20% w / w zeolite and wherein the zeolite polymer matrix lacks interfacial voids or wherein the voids are less than 20 nm measured at their longest dimension.
2. The MMM according to claim 1, wherein the membrane comprises a glassy polymer matrix having at least 30, 40 or 50% w / w zeolite.
3. The MMM according to claim 1 or 2, wherein the zeolite is a plate-shaped, cube-shaped, rectangular parallelepiped-shaped, spherical-shaped or octahedral-shaped zeolite.
4. The MMM of any one of claims 1 to 3, wherein the zeolite is in the form of flakes and has a concentration of at least 20% w / w, at least 30% w / w, at least 40% w / w, or at least 50% w / w in the membrane.
5. The MMM according to any one of claims 1 to 4, wherein the membrane has a concentration of at least 40% w / w zeolite and has a CO2 permeability of at least 4000 barrer.
6. The MMM according to any one of claims 1 to 5, wherein the membrane has a concentration of at least 20% w / w zeolite / polymer and has a CO2 / CH4 selectivity of >100.
7. The MMM according to any one of claims 1 to 5, wherein the membrane has a concentration of at least 40% w / w zeolite and has a CO2 / CH4 selectivity of >400.
8. The MMM according to any one of claims 1 to 7, wherein the zeolite is in the shape of flakes.
9. The MMM according to any one of claims 1 to 8, wherein the zeolite is an 8 or 12 membered ring.
10. MMM according to any one of claims 1 to 9, wherein the zeolite is of AEI type.
11. The MMM according to any one of claims 1 to 10, wherein the membrane is flexible and has a flexural modulus between 2 up to 9 GPa.
12. The MMM according to any one of claims 1 to 11, wherein the membrane is flexible and has a flexural modulus between 3.5 and 9 MPa.
13. The MMM according to any one of claims 1 to 12, wherein the polymer is a polyimide.
14. A method for preparing a mixed matrix membrane, the method comprising the steps of: a) preparing a glassy polymer and zeolite mixture in a solvent, wherein the solvent comprises at least 5% w / v polymer and comprises at least 20, 30, 40 or 50% w / w zeolite, b) pouring the mixture obtained in step a), c) drying the casting mixture obtained in step b) to obtain a membrane, wherein said drying is carried out at a rate such that between 85 and 95% by weight of the solvent is removed within a period of time between 15 minutes and 24 hours, d) heating the dried film obtained in step c) at a temperature below the glass transition temperature of the polymer, wherein the heating is maintained for a period of time between 5 minutes and 24 hours and / or is performed at a temperature between 30 and 300° C., provided that the temperature is below the transition temperature of the polymer.
15. The process according to claim 14, wherein the solution of the polymer and the dispersion of the zeolite are prepared separately and subsequently mixed.
16. A process according to claim 14 or 15, wherein the drying in step c) is carried out at a rate such that between 85 and 95% by weight of the solvent is removed over a period of between 5 minutes and 24 hours.
17. A process according to claim 14 or 15, wherein the drying in step c) is carried out at a rate such that between 85 and 95% by weight of the solvent is removed over a period of between 3 and 24 hours.
18. The method according to any one of claims 14 to 17, wherein in step d, the film is heated at a temperature between 30°C and the glass transition temperature of the polymer.
19. A method according to any one of claims 14 to 17, wherein in step d, the film is heated at a temperature between 120 or 150°C and the glass transition temperature of the polymer.
20. The process according to any one of claims 14 to 19, wherein the heating in step d) is maintained for a period of between 4 hours and 24 hours.
21. The process according to any one of claims 14 to 19, wherein the heating in step d) is maintained for a period of between 8 hours and 24 hours.
22. The process according to any one of claims 14 to 19, wherein the heating in step d) is maintained for a period of between 8 hours and 24 hours and / or wherein step d) is performed at a temperature between 150°C and 300°C.
23. A method according to any one of claims 14 to 22, followed by a step wherein the absence of a void is determined.
24. The method of claim 23, wherein the absence of voids is determined by microscopy.
25. The method of claim 23, wherein the absence of voids is determined by measuring the flow rate of a gas over the membrane.
26. The method of any one of claims 14 to 25, wherein the zeolite is in the form of flakes.
27. A process according to any one of claims 14 to 26, wherein the zeolite is of the AEI type.
28. The method of any one of claims 14 to 27, wherein the polymer is a polyimide.